Bollywood baddies : villains, vamps, and henchmen in Hindi cinema - Ghosh, Tapan Kumar (Professor) (SAGE Publications, 2013)
Bollywood Baddies is the first-of-its-kind book-length narrative of villainy in Hindi films. It discusses villains, vamps, and henchmen of Bollywood cinema, and also the actors who essayed such characters over the decades. The author discusses not just villains but also the evaluation of villainous characters vis-à-vis sociopolitical conditions in the country. The narrative begins with Ashok Kumar's negative role in Kismet as early as 1943, and goes up to the Agneepath remake (2012), where Sanjay Dutt plays Kancha Cheena, earlier essayed by Danny Denzongpa in the original.